Therapeutic guidelines for antimicrobial use in chronic suppurative otitis media for a tertiary care hospital in Sub Himalayan region - Sawaraj, Sushma; Dogra, Sunder Singh; Kansal, Dinesh; Thakur, Kamlesh; Sharma, Parveen Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The battle against micro-organisms, in their role as primary cause of the disease and infective complications of medical and surgical techniques, has not decreased in spite of modern antimicrobial therapy. Chronic suppurative otitis media (CSOM) is a disease with worldwide prevalence having potentially serious long term effects. The disease remains an important global public health problem leading to hearing impairment, and due to wide spread irrational use microbial resistance is very common to these antibiotics, thereby leading to treatment failure. Hence it is important to know the type of bacteria and their sensitivity pattern so that appropriate antibiotics may be given for treatment and prevention of complications. Methods: 428 patients of otitis media were enrolled from ENT OPD of Tertiary Care Hospital. Ear swab was taken from diagnosed cases of CSOM and culture and sensitivity were done. Results: The microbiology of the swab showed no growth in (25.4%) of samples. Staphylococcus aureus (26%) and Pseudomonas (25%) were the main organisms isolated. Staphylococcus aureus isolated was sensitive to vancomycin, clindamycin, cefixime, gentamicin and cefipime in descending order. Pseudomonas aeruginosa was sensitive to ceftazidime, imipenem, piperacillin, gentamicin, cefipime. In the present study Staph. aureus and Pseudomonas were the predominant bacteria, it is suggested to undertake a gram staining in all patients. If gram positive organisms are isolated it is suggested that presumptive treatment should be directed against Staphylococcus aureus and if gram negative then against Pseudomonas aeruginosa. Such a treatment is not only likely to be effective but will also go a long way in preventing emergence of drug resistance. Conclusions: The antimicrobial therapy should be based on locally determined microbiological isolates and local sensitivity patterns to a particular antimicrobial agent. The presumptive antimicrobial therapy should therefore be directed against these organisms.